Translation of Diogenes Laërtius’ Vitae Philosophorum, Book IV: On the Academics - Brito, Rodrigo Pinto de (2018)
Translation of Diogenes Laërtius’ Lives, book 4, dealing with the Academic thinkers after Plato.